2004
DOI: 10.1001/archopht.122.9.1324
|View full text |Cite
|
Sign up to set email alerts
|

Visual Fields in Retinoblastoma Survivors

Abstract: To describe the visual field defects in retinoblastoma survivors and relate those defects to characteristics such as tumor size, tumor location, and treatment modality.Methods: Thirty-one patients treated for retinoblastoma were included in this study. Humphrey visual fields were determined in 33 eyes.Results: Twenty-seven patients (29 eyes, 68 tumors) had sufficient diagnosis and treatment data available for further analysis. Twenty-six of the 27 patients had both absolute and relative visual field defects. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…To the best of our knowledge, the current study is the largest study to date to assess the medical outcomes and general health of adult survivors of Rb. Although extensive data exist regarding the risk of SMN and oculovisual outcomes in survivors of Rb, there is a paucity of information regarding chronic medical conditions in this population. In the current report, we found that adult survivors of Rb were 1.4 times more likely to report any chronic condition, and 7.6 times more likely to have a severe or life‐threatening chronic condition, when compared with a similarly aged cohort of individuals without a history of Rb.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the current study is the largest study to date to assess the medical outcomes and general health of adult survivors of Rb. Although extensive data exist regarding the risk of SMN and oculovisual outcomes in survivors of Rb, there is a paucity of information regarding chronic medical conditions in this population. In the current report, we found that adult survivors of Rb were 1.4 times more likely to report any chronic condition, and 7.6 times more likely to have a severe or life‐threatening chronic condition, when compared with a similarly aged cohort of individuals without a history of Rb.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with retinoblastoma demonstrate a variety of long-term defects in visual function, particularly in visual acuity, after treatment for their intraocular disease. These defects are related to tumour size, location and treatment method 6. One study of visual acuity following treatment with systemic chemotherapy and local ophthalmic therapy was conducted in 54 eyes from 40 children.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment regimens include local treatment, chemotherapy, irradiation and/or enucleation, and result in an overall survival >95%. However, long-term sequelae, including secondary tumours and compromised vision, are common among survivors 5 6…”
Section: Introductionmentioning
confidence: 99%
“…Children that repeatedly do not respond to stimuli in a particular quadrant, or whose parents describe problems that point to a peripheral scotoma, deserve a careful examination of the corresponding retinal area for matching pathology. A study of 27 patients with treated retinoblastoma demonstrated a variety of scotoma patterns, which, at times, correctly corresponded to tumor location, but at other times corresponded poorly and were larger than clinically expected [3]. We should be careful not to overlook or underestimate the size and functional importance of these visual field defects.…”
Section: Visual Limitation Beyond Acuitymentioning
confidence: 96%